Optimalisasi Kinerja Karyawan Dalam Pengembangan Organisasi Bisnis - Maskarto Lucky Nara Rosmadi (Institut Agama Islam Negeri Madura, 2018)
This research is to know the influence of career development, training, and reward on employee performance of PT. Sinjaraga Santika Sport. The method used is path analysis. Based on result of research, partially effect of career training development, and reward give contribution respectively 28,60%, 27,20%, and 20,70% to employee performance. The effect of simultaneously career development, training, and reward on employee performance is equal to 0,765 or 76,50%, while 0,235 or 23,50% influenced by other variable not examined in this research. From the results of research conducted, the career development variables training, and rewards when combined will have a significant effect on employee performance. From the results of the above research, it can be concluded that employee career development is very dominant for the progress of business organizations in the future.